Filipino Senior High School Students’ Perceived Stress and Coping Strategies in the Post-Pandemic Context - Celosteo A Villaceran (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to determine the levels of perceived stress and coping strategies among Filipino senior high school students in the post-pandemic context and to examine the relationships between their stress and coping strategies. Methodology: The study employed a descriptive-correlational design using validated survey instruments, namely the Perceived Stress Scale (PSS-10) and the Filipino Coping Strategies Scale (FCS). Data were collected through an online self-administered questionnaire among senior high school students in Central Visayas, Philippines, following ethical and consent procedures. The data were analyzed using SPSS, applying descriptive statistics (mean and standard deviation) and Pearson product–moment correlation to examine the relationship between perceived stress and coping strategies. Main Findings: Students reported high levels of perceived stress and generally high coping strategies, with religiosity being very high. Moderate coping strategies included overactivity and emotional release, while substance use was low. Correlations showed negligible but significant positive relationships between stress and most coping strategies, except religiosity, which was not significant. Novelty/Originality of this study: This study integrates the Transactional Theory of Stress and Coping with the Grounded Theory of Filipino Well-Being (Kaginhawaan), providing culturally contextualized insights into student stress and coping in the post-pandemic era. It advances knowledge by highlighting Filipino-specific coping mechanisms and their relevance in educational and guidance practices, offering practical implications for supporting student resilience.